Knowledge, attitude and practice about allergic rhinitis in a rural population, Kancheepuram district, Tamil Nadu - Rajasekaran, Valli; Ghosh, Puja (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Allergic rhinitis presents a global health problem. The lack of awareness about allergic rhinitis leads to poor adherence to management protocol. Methods: Our cross sectional study in 100 patients with allergic rhinitis was aimed at assessing the knowledge, attitude and practice about the disease. This was done using a questionnaire. Descriptive analysis was made in the three domains and expressed in percentage. Results: The knowledge about the cause and the treatment options was low. Most of the patients were worried about the long term side effects and dependence of the drugs used for treatment of allergic rhinitis. Most patients ignore the symptoms and do not seek medical advice. Conclusions: Improving the patient’s knowledge and attitude through health education can improve practices among allergic rhinitis patients.